Internet Of Things Based Smart Home System Using ESP32 Microcontroller - Beki, Cyril; Sahari, Norain; Ismail, Noramin (Progress in Engineering Application and Technology, 2020)
Nowadays, people tend to forget switching OFF their appliances especially heavy load at home causing their electricity bill to raise drastically. Apart from that, there is some people that are unable to walk to switch ON and OFF the appliances due to their health condition forcing them to either let it stay ON or ask others to help them but bear in mind they will not always be by their side. Additionally, in this current era toward the development of technologies, most of people are getting addicted to automatic devices which they believe can transform and ease their life especially in work. Internet of Things (IoT) manage to fulfil these criteria and give people a better quality of life. In this project, Internet of Things Based Smart Home System Using ESP32 Microcontroller is built to ease people especially in helping disable people. It can save their time if they are away from their home to turn on and off the electrical appliances and assist those in need to perform their daily task easily. This smart technique involves operating the switches through online server of a mobile or a computer. The project uses Ubidots STEM MQTT server and ESP32 to control ON and OFF of electrical appliances such as light. Instead, it can be control manually or online according to the user desire and will updates the status of appliances to the Ubidots STEM control panel.